Analisis Kesesuaian Lokasi Fasilitas Kesehatan Pariwisata dengan Pendekatan Network dan SMCA–AHP di Kecamatan Kuta Selatan - Talakua, Jossh Christheyn Endrew; Pangestika, Rendiana Satya; Rifai, Ahmad (Journal of Geographical Sciences and Education, 2025)
The rapid growth of the tourism sector has increased the need for equitable, accessible, and supportive healthcare facilities. This study aims to analyze the spatial accessibility of healthcare facilities and assess the suitability of new development locations in relation to the physical, social, and infrastructural conditions of the region. The method used combines Network analysis to assess service coverage and access efficiency, and Spatial Multicriteria Analysis (SMCA) with the Analytical Hierarchy Process (AHP) approach to assign weights to eight location-determining criteria. The distribution of healthcare facilities in South Kuta District is uneven, with an average distance of 2,217.89 meters between tourist attractions and healthcare facilities. Pecatu and Kutuh Villages have low accessibility to healthcare services. Pecatu Village and Kutuh Village have low accessibility to health services, while Jimbaran Subdistrict and Pecatu Village are the areas with the highest level of suitability for health facility development. The integration of Network analysis and SMCA–AHP has proven effective in supporting the sustainability of healthcare-based tourism areas in South Kuta.